2006
DOI: 10.1007/s15010-006-5013-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Interleukin-18 (IL-18), Interleukin-1β (IL-1β), its Soluble Receptor sIL-1RII and C-reactive Protein (CRP) in Patients with Lyme Arthritis

Abstract: The results of our study suggest that IL-18, IL-1beta and sIL-1RII might be involved in the development of LA. CRP may be useful in differential diagnosis in patients with suspicion of Lyme arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…All three pointed to a lack of substantially enhanced systemic CRP response in most patients with Lyme arthritis [21][22][23], in agreement with our results. A serum analysis in 20 patients with early neurologic Lyme disease reported a lack of increased CRP concentration in most [24], while a study of 44 Lyme disease patients with EM found both CRP and SAA to be significantly elevated in comparison to 23 healthy controls [25]. Our data confirm these findings as well.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All three pointed to a lack of substantially enhanced systemic CRP response in most patients with Lyme arthritis [21][22][23], in agreement with our results. A serum analysis in 20 patients with early neurologic Lyme disease reported a lack of increased CRP concentration in most [24], while a study of 44 Lyme disease patients with EM found both CRP and SAA to be significantly elevated in comparison to 23 healthy controls [25]. Our data confirm these findings as well.…”
Section: Discussionsupporting
confidence: 92%
“…non-Lyme arthritis, without incorporating healthy controls [21,22], and one study examined CRP levels in 20 Lyme arthritis patients and 10 healthy volunteers [23]. All three pointed to a lack of substantially enhanced systemic CRP response in most patients with Lyme arthritis [21][22][23], in agreement with our results.…”
Section: Discussionsupporting
confidence: 85%
“…126 Curiously, the Arg112Cys and Ile164Thr mutations that prevent adiponectin from trimer formation and result in the impaired secretion of this protein from the cell were shown to be clinically associated with hypoadiponectinemia. 80 Intercellular cell adhesion molecule-1 (iCAM-1), also known as CD54 (cluster of differentiation 54), is an immunoglobulin-like glycoprotein expressed on the surface of several cell types including endothelial cells and cells involved in the immune response, 128 where it serves as a ligand for the leukocyte adhesion protein LFA-1 (integrin a-L/b-2). Besides its major role in stabilizing cell-cell interactions and facilitating leukocyte endothelial transmigration, iCAM-1 serves as a site for the cellular entry of human rhinovirus 129,130 and is involved in a signal transduction 131 and spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A role for IL-1␤ has been suggested in Lyme borreliosis because IL-1␤ mRNA can be detected in erythema migrans lesions of patients with Lyme disease, and elevated levels of the cytokine can be found in their sera (31,35). In addition, human peripheral blood mononuclear cells secrete IL-1␤ after ingestion of live B. burgdorferi spirochetes (15).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1␤, however, may play a role because human peripheral blood mononuclear cells secrete IL-1␤ after ingestion of live B. burgdorferi spirochetes (15). In support of this hypothesis, serum levels of IL-1␤ were reported to be elevated in Lyme disease patients, and the levels decreased significantly after doxycycline treatment (35). IL-1␤ mRNA levels in erythema migrans lesions were also shown to be elevated (31).…”
mentioning
confidence: 94%